Pengaruh investasi swasta dan pengeluaran pemerintah daerah terhadap pertumbuhan ekonomi dan pengangguran di kabupaten malinau (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
This study aimed to find out and analyze the influence of private investment directly to economic growth in Malinau, identify and analyze the influence of local government spending directly to economic growth in Malinau, identify and analyze the influence of private investments directly against unemployment in Malinau, identify and analyze the influence of local government spending directly to unemployment in Malinau, identify and analyze the influence of private investments indirectly against unemployment through growth ekonomidi Malinau District, identify and analyze the influence of local government spending indirectly against unemployment through growth ekonomidi Malinau District, know and analyze the effect of the growth of direct ekonomisecara against unemployment in Malinau. The results of the study can be explained as follows: Private investment provides a significant and positive effect on economic growth in Malinau. Local government spending had a negative impact and no significant effect on economic growth in Malinau. Private investments have a positive impact and no significant effect on unemployment in Malinau. Local government spending had a positive influence and significant impact on unemployment in Malinau. Economic growth had a positive influence and no significant effect on unemployment in Malinau.